Diversity of plant species in paddy ecosystem in West Sumatra, Indonesia - ENIE TAURUSLINA AMARULLAH; TRIZELIA TRIZELIA; YAHERWANDI YAHERWANDI; HASMIANDY HAMID (Society for Indonesian Biodiversity, 2017)
Tauruslina EA, Trizelia, Yaherwandi, Hamid H. 2017. Diversity of plant species in paddy ecosystem in West Sumatra. Biodiversitas 18: 1218-1225. Community is a group of living things which have adjusted and inhabited a natural habitat. Characteristics of the community in an environment are its diversity. The diversity of the plants is a plant species that occupy an ecosystem. The research was aimed at determining species diversity, the dominance of plant species and summed dominance ratio (SDR) in paddy ecosystem. The plant samples were taken from the location of endemic areas of brown plant hopper in Tanjung Mutiara Subdistrict, Agam District West Sumatra. Sampling was done by using two methods, (i) survey methods with direct data collection; (ii) squares method, observation of sample plots in the field. The level of diversity of plant species was analyzed using diversity index of Shannon-Wiener (H’). Plant species dominance was analyzed using dominance index (C). The results showed that index value of Shannon-Wienner ranged 1.00 – 1.73, which indicated that the category of diversity level of plants was medium. Dominance index ranged 0.03 - 0.08 which meant there were a dominant species among the plants in the study areas. The highest SDR in the ecosystem type III were Cyperus rotundus (40.87%) and Borreria laevis (37.43%), in the type I was C. rotundus (34.90%) and in type II was Portulaca oleracea (20.08%). The dominant plant species found in the type I were C. rotundus, Eleusine indica, Borreria laevis, in type II were P. oleracea, C. rotundus, Amaranthus spinosus and in type III were C. rotundus, B. laevis, and A. spinosus.